Enhancing learning in the context of Street football: a case for Nonlinear Pedagogy. (4th March 2019) - Machado, João Cláudio; Barreira, Daniel; Galatti, Larissa; Chow, Jia Yi; Garganta, Júlio; Scaglia, Alcides José
ABSTRACT: Background: Street football can be understood as the most natural way to learn football and it can be a great starting point to develop perceptual, decisional, tactical and motor skills. Importantly, players involved in Street football may develop a strong emotional bond to the game through their experiences playing in an informal setting and eventually this could support their participation in a more structured playing environment. However, nowadays, talented children have reduced opportunities to play the game in this informal environment and instead, are mostly experiencing the game through their participation in organised settings such as in youth football clubs and academies. Importantly, such structured and formal environments afford the children a more rigid and less representative learning environment, which could potentially inhibit the development of creativity and adaptability among these young players. Purpose: The current paper aims to discuss the importance of Street football to players' development and the role of a Nonlinear Pedagogy (NLP) framework to support the design of a player-centred and game-based approach that can contribute to enhance learning of creative and adaptive behaviours in football. Discussion: Pedagogical principles of NLP (representative learning design, information-movement couplings, manipulation of constraints, exploratory learning and reducing conscious control of movement) underpinned by concepts from Ecological Dynamics and working through pedagogical channels (instruction, feedback and practice) can facilitate the design of representative training tasks to enhance learning. NLP emphasises a learner-centred approach and highlights the critical role that the practitioner plays as a facilitator in providing learners with meaningful practice that leads to effective transfer of game-play behaviours. Street football affords features that capture some of the above key pedagogical principles and presents a suitable platform to support the acquisition of game-play behaviour that is meaningful for the individual learner. Conclusions: Through a recognition of the current need to design a football learning environments that capture key elements of Street football, we highlight the relevance of NLP as a pedagogical framework to underpin a learner-centred and game-based approach, supporting practitioners with a set of pedagogical principles. Thus, we propose that through this representative learning environment we can enhance learning in football and contribute to the development of intelligent and creative players.